2020
DOI: 10.1098/rsos.191590
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on photocatalytic activity of transition metals (Ag and Ni)-doped ZnO nanomaterials synthesized via sol–gel method

Abstract: Ag and Ni/ZnO photocatalyst nanostructures were successfully synthesized by a sol–gel method. In this work, the photocatalyst sample was systematically studied based on several factors affecting the performance of photocatalyst, which are size, morphology, band gap, textural properties and the number of active sites presence on the surface of the nanocatalyst. X-ray diffraction revealed that Ag/ZnO nanomaterials experienced multiple phases, meanwhile for Ni/ZnO the phase of nanomaterials were pure and single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 58 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…In comparison to the CO 2 -TPD result for sample F, the enhanced CO 2 -TPD signal for sample E at 120 °C indicates the enhanced basicity of Ni cooperated with ZnO at the interface compared to Ni only. This peak at 120 °C is dominant in the figure, suggesting a significant increase of CO 2 adsorption on the interface after the addition of a small amount of Zn (1 wt % Zn in sample E). The peak at 507 °C is attributed to CO 2 adsorbed on ZnO. …”
Section: Resultsmentioning
confidence: 99%
“…In comparison to the CO 2 -TPD result for sample F, the enhanced CO 2 -TPD signal for sample E at 120 °C indicates the enhanced basicity of Ni cooperated with ZnO at the interface compared to Ni only. This peak at 120 °C is dominant in the figure, suggesting a significant increase of CO 2 adsorption on the interface after the addition of a small amount of Zn (1 wt % Zn in sample E). The peak at 507 °C is attributed to CO 2 adsorbed on ZnO. …”
Section: Resultsmentioning
confidence: 99%
“… 24 Whereas, Jeyachitra et al 25 have reported the synthesis of Ni and Ag codoped ZnO NPs for dye degradation applications. Azfar et al 26 have also reported the synthesis of Ni and Ag codoped ZnO NPs by using the sol–gel method. Recently, Sachi et al 27 reported the synthesis of NiAg@ZnO nanocomposites by in situ chemical co-reduction method and their applications in nitro-compounds reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For more efficient and low-cost utilization photodegradation schemes, the utilization of light in the visible region of the solar spectrum which constitutes about 40-50% of the entire solar spectrum must be considered [17,18]. Some of the methods that have been widely explored to improve the visible light responsiveness of wide-bandgap semiconductors photocatalyst include doping [19], dye sensitization [4,20], and surface property modification [13]. Despite the research efforts been exerted in trying to improve the visible responsiveness of wide-bandgap semiconductor photocatalyst [21].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, perovskite structured LaMnO3 was utilized to effectively degrade rhodamine B dye [23]. Some of the reports indicate the usefulness of perovskite structured LaMnO3 and its modified forms in the photodegradation of various organic dyes [17][18][19][20][21][22][23]. Given the successes LaMnO3 recorded as a photocatalyst, it is interesting that little work is done on its utilization as an efficient photocatalyst for the degradation and mineralization of recalcitrant emerging pollutants.…”
Section: Introductionmentioning
confidence: 99%